Examination of Combined Effect of Porous Material and Corrugated Wall on Convection Heat Transfer in A Conduit - Kamisli, Fethi; Algıbara, Musaa (My University, 2025)
In this research, a simulation was carried out to investigate the combined effect of the presence of a porous medium in a channel and semicircular sections on its upper wall on non-Darcian flow and forced convection heat transfer. The simulation of the created model was done by solving the dimensionless constitutive equations using the COMSOL multiphysics program (v.6.1). The effects of process parameters such as the radius of semicircular sections (R) and the distance between centers of semicircular sections (Lc), Reynolds number (Re) and Darcy number (Da) on the convection heat transfer were investigated. The results showed that the heat transfer rate increased with increasing radius, distance between sections, and Reynolds number. The maximum heat transfer rate was obtained at radius (R = 0.75H), distance between sections (Lc = 9R), and Reynolds number (Re = 200). The values for velocity and Nusselt number obtained in the study were compared with the values obtained in similar studies to check whether the program gave correct results. It was observed that the Nusselt number values obtained in this study, as in similar studies, decreased asymptotically and remained constant at the value of 5. It was found that the results of the present study were in good agreement with those of the previous related studies.
Keywords: Forced convection; Non-Darcian flow; porous medium; semi-circular sections